Sémiotique narrative de la joie dans The River between de Ngugi Wa Thiong’o - Abib Sene (Multilinguales)
Omnipresent in Ngugi Wa Thion’go’s fictional work, the theme of joy stands as a meaning ful sign in the verbal and physical interactions of the characters of his novel The River Between. Our objective in this paper is to highlight the semiotic aspect of the narration of “Chrislike” and “customary” joys. We will also point out the difference between the already mentioned forms of joy and their social and religious impact on the Kikuyu society. To achieve this objective, a study of the social practices of female genital mutilation and circumcision will underlie our analysis.